Effect of Remote Cardiac Monitoring System Design on Response Time to Critical Arrhythmias. Issue 2 (10th April 2022) - Segall, Noa; Joines, Jeffrey A.; Baldwin, Ron'Nisha D.; Bresch, Diane; Coggins, Lauren G.; Janzen, Suzanne; Engel, Jill R.; Wright, Melanie C.
Abstract : Introduction: In many hospitals across the country, electrocardiograms of multiple at-risk patients are monitored remotely by telemetry monitor watchers in a central location. However, there is limited evidence regarding best practices for designing these cardiac monitoring systems to ensure prompt detection and response to life-threatening events. To identify factors that may affect monitoring efficiency, we simulated critical arrhythmias in inpatient units with different monitoring systems and compared their efficiency in communicating the arrhythmias to a first responder. Methods: This was a multicenter cross-sectional in situ simulation study. Simulation participants were monitor watchers and first responders (usually nurses) in 2 inpatient units in each of 3 hospitals. Manipulated variables included: (1) number of communication nodes between monitor watchers and first responders; (2) central monitoring station location—on or off the patient care unit; (3) monitor watchers' workload; (4) nurses' workload; and (5) participants' experience. Results: We performed 62 arrhythmia simulations to measure response times of monitor watchers and 128 arrhythmia simulations to measure response times in patient care units. We found that systems in which an intermediary between monitor watchers and nurses communicated critical events had faster response times to simulated arrhythmias than systems in which monitor watchers communicated directly with nurses. Responses were also faster in units colocated with central monitoring stations than in those located remotely. As the perceived workload of nurses increased, response latency also increased. Experience did not affect response times. Conclusions: Although limited in our ability to isolate the effects of these factors from extraneous factors on central monitoring system efficiency, our study provides a roadmap for using in situ arrhythmia simulations to assess and improve monitoring performance.